157. A Multidisciplinary Approach to Carbapenem Stewardship at a Large Community Hospital in Brooklyn, New York. (31st December 2020) - Simon, Samuel; Li, Rosanna; Lin, Yu Shia; Mayer, Suri; Chapnick, Edward; Ghitan, Monica
Abstract: Background: Carbapenem-resistant gram-negative organisms are a continuously mounting threat, underscoring the need for effective antimicrobial stewardship interventions to improve the use of carbapenems. We sought to implement several multidisciplinary antimicrobial stewardship interventions beginning in January 2019 in an effort to reduce unnecessary meropenem use and the incidence of carbapenem-resistant gram-negatives. Methods: Prospective audit and feedback was utilized daily in combination with weekly stewardship rounds between an Infectious Diseases pharmacist and physician in the Intensive Care Units. A second Infectious Diseases physician attended weekly interdisciplinary rounds on meropenem high-use units. Meropenem Days of Therapy (DOT) per 1, 000 patient days and the incidence of meropenem resistant Pseudomonas aeruginosa and Klebsiella pneumoniae were compared by the chi-square test of proportions. Results: Between 2018 and 2019 the institution's meropenem DOT per 1, 000 patient days decreased 33%, from 57 to 38 days per 1, 000 patient days (difference, 19 days per 1, 000 patient days; p< 0.001). In the hospital antibiogram, the meropenem susceptibility of Pseudomonas aeruginosa over the same time period increased from 71% to 77% of isolates (difference, 6%; p = 0.009). A non-significant decrease in the susceptibility of meropenem to Klebsiella pneumonia e was also observed from 92 to 90% (difference, 2%: p = 0.1658). Conclusion: These data support the need for antimicrobial stewardship efforts targeting broad-spectrum antimicrobials such as meropenem. In the setting of a sustained decrease in meropenem use over 12 months, we observed a significant improvement in the percent susceptibility rate of Pseudomonas aeruginosa to meropenem for the first time in five years. Disclosures: All Authors : No reported disclosures